Tinjauan Yuridis Pemberlakuan Pemberatan Pidana Terhadap Residivis Penyalahgunaan Narkotika - Ramadhanti, Aghniya Erlita; Wadjo, Hadibah Zachra; Taufik, Iqbal (PATTIMURA Law Study Review, 2024)
ABSTRACT: There are serious concerns regarding drug abuse in Indonesia, which has spread to various levels of society. This phenomenon has also become a global concern due to its detrimental impact. Law No. 35/2009 on Narcotics is the legal basis that regulates supervision, control, and sanctions against perpetrators of narcotics abuse. However, there are cases of drug abuse recidivists, such as the case of Dedi Ismail Yusuf Manilet, which shows a discrepancy between law enforcement and existing regulations. Dedi, who is a recidivist offender of narcotics abuse in a period of less than three years, in the second verdict did not receive criminal aggravation in accordance with applicable regulations. The purpose of this research is to analyze and examine the mechanism of punishment against perpetrators of narcotics abuse based on Law Number 35 of 2009 concerning Narcotics and the reasons why the judge did not impose criminal aggravation on the defendant in court decision No. 145/PidSus/2022/PNAmb. The research method, the author uses normative juridical research based on the main legal material by examining the theories and laws and regulations related to this research. The results of this research can be concluded that the mechanism of punishment against perpetrators of narcotics abuse based on Law Number 35 of 2009 concerning Narcotics can be imprisoned for a maximum of 4 years depending on the class of narcotics and can be rehabilitated under certain conditions. The reason why the judge did not aggravate the punishment against the defendant in court decision number 145/Pid.Sus/2022/PN.Amb is that there were defects in the procedure for imposing criminal sanctions against the perpetrator starting from the police, the prosecutor's office who did not charge the perpetrator with criminal aggravation, then in the end the judge in deciding the case was in line with the prosecutor's demands and charges and in his decision the judge did not pay attention to the fact that the defendant was a recidivist and did not pay attention to the defendant's statement that he had used methamphetamine and marijuana which the defendant stated during the trial.